A FMEA-based Approach to Identify Risk of Damage for Besuki Na-Oogst Tobacco Leaves - Wibowo, Yuli; Rusdianto, Andrew S; Wahyuni, Septy T (AGRITEKNO: Jurnal Teknologi Pertanian, 2021)
Besuki Na-Oogst tobacco is a type of plantation commodity that requires special handling. Improper post-harvest handling increases the risks of being damaged. This study aimed to identify the types of damage to Besuki Na‑Oogst tobacco leaves, analyze the risk level of damage to Besuki Na-Oogst tobacco leaves, and provide recommendations for risk control of tobacco leaves damage. The Failure Mode and Effect Analysis method was applied to Identify the Besuki Na-Oogst tobacco leaves risk damages. This method can determine the value of severity, occurrence, and detection to obtain a critical Risk Priority Number (RPN) that indicates the most critical level of risk. The results showed that the types of damage to Besuki Na-Oogst tobacco leaf classified as having a high-risk impact were perforated leaves, oily leaves, white spots, blue spots, and moldy leaves indicated by RPN values greater than the critical value. If these risks are not appropriately handled, it can decrease the quality of the tobacco leaves, resulting in losses. The risk control of leaf damage is based on risk-causing factors in suggestions for improvements that the management can follow up. Keywords: Besuki Na-Oogst tobacco leaves; critical value; FMEA; risk; RPN ABSTRAK Tembakau Besuki Na-Oogst merupakan jenis komoditas perkebunan yang memerlukan penanganan khusus. Penanganan pasca panen yang tidak tepat menimbulkan risiko yang tidak diinginkan yaitu daun tembakau menjadi rusak. Penelitian ini bertujuan untuk mengidentifikasi jenis kerusakan daun tembakau Besuki Na-Oogst, menganalisis tingkat risiko kerusakan daun tembakau Besuki Na-Oogst, dan memberikan rekomendasi pengendalian risiko kerusakan daun tembakau. Identifikasi risiko kerusakan daun tembakau Besuki Na-Oogst menggunakan metode Failure Mode and Effect Analysis. Metode ini dapat digunakan untuk menentukan nilai keparahan, kejadian, dan deteksi untuk mendapatkan risk priority number kritis yang menunjukkan tingkat risiko paling kritis. Hasil penelitian menunjukkan bahwa jenis kerusakan pada daun tembakau Besuki Na-Oogst yang tergolong berisiko tinggi adalah daun berlubang, daun berminyak, bercak putih, bercak biru, dan daun berjamur yang ditunjukkan dengan nilai RPN lebih besar dari nilai kritis. Jika risiko tersebut tidak ditangani dengan baik, maka daun tembakau akan mengalami penurunan kualitas yang dapat mengakibatkan kerugian. Pengendalian risiko kerusakan daun tembakau didasarkan pada faktor penyebab risiko berupa saran perbaikan yang dapat ditindaklanjuti oleh pihak perusahaan. Kata kunci: Daun tembakau Besuki Na-Oogst; FMEA; nilai kritis; risiko; RPN